1999
DOI: 10.1063/1.1149892
|View full text |Cite
|
Sign up to set email alerts
|

Radio-frequency impedance measurements using a tunnel-diode oscillator technique

Abstract: A resonant method based on a tunnel-diode oscillator (TDO) for precision measurements of relative impedance changes in materials, is described. The system consists of an effective self-resonant LCtank circuit driven by a forward-biased tunnel diode operating in its negative resistance region. Samples under investigation are placed in the core of an inductive coil and impedance changes are determined directly from the measured shift in resonance frequency. A customized low temperature insert is used to integrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 10 publications
0
43
0
Order By: Relevance
“…The TS has been a largely successful technique for directly probing magnetic anisotropy in assemblies of single domain particles. 28,29 This method measures the susceptibility by means of a perturbing alternating current field (H AC ) oriented perpendicular to a changing direct current (DC) magnetic field, H DC . In the theoretical paper on the transverse susceptibility of a Stoner Wohlfarth particle, Aharoni et al calculated that three singularities would be observed in the transverse susceptibility when H DC was scanned from positive to negative saturation.…”
Section: Resultsmentioning
confidence: 99%
“…The TS has been a largely successful technique for directly probing magnetic anisotropy in assemblies of single domain particles. 28,29 This method measures the susceptibility by means of a perturbing alternating current field (H AC ) oriented perpendicular to a changing direct current (DC) magnetic field, H DC . In the theoretical paper on the transverse susceptibility of a Stoner Wohlfarth particle, Aharoni et al calculated that three singularities would be observed in the transverse susceptibility when H DC was scanned from positive to negative saturation.…”
Section: Resultsmentioning
confidence: 99%
“…The measurements were done using a LC-tank resonator driven by a tunnel diode forward biased in its negative resistance region. This idea is the basis of the TDO measurement system whose circuit design and operation have been described elsewhere in detail [9]. The circuit is self-resonant with a typical resonance frequency around 5MHz.…”
Section: Methodsmentioning
confidence: 99%
“…To probe the dynamic transverse susceptibility in the radio-frequency range we employed a very sensitive method that we have recently developed [9]. Our experiments are based on a novel tunnel-diode oscillator (TDO) technique that combines the advantages of the precision afforded by resonance frequency measurements along with the transverse modulation principle.…”
Section: Methodsmentioning
confidence: 99%
“…The magnetic anisotropy and switching fields in the samples were probed by TS using a sensitive, self resonant tunnel diode oscillating (TDO) technique 11 with a resonant frequency of $20 MHz. The sample was placed in the inductance coil of the tank circuit integrated into the PPMS.…”
mentioning
confidence: 99%